2020
DOI: 10.3390/cells9030765
|View full text |Cite
|
Sign up to set email alerts
|

Looking at New Unexpected Disease Targets in LMNA-Linked Lipodystrophies in the Light of Complex Cardiovascular Phenotypes: Implications for Clinical Practice

Abstract: Variants in LMNA, encoding A-type lamins, are responsible for laminopathies including muscular dystrophies, lipodystrophies, and progeroid syndromes. Cardiovascular laminopathic involvement is classically described as cardiomyopathy in striated muscle laminopathies, and arterial wall dysfunction and/or valvulopathy in lipodystrophic and/or progeroid laminopathies. We report unexpected cardiovascular phenotypes in patients with LMNA-associated lipodystrophies, illustrating the complex multitissular pathophysiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 58 publications
2
7
0
Order By: Relevance
“…ITPR3 singlenucleotide polymorphism rs2229634 could be indicative of an increased incidence in coronary artery aneurysm among youngsters [36]. Variants in LMNA are linked with lipodystrophy [37]. Combining previous research, these mRNAs identified by this study may possess tight links to CAD pathogenesis.…”
Section: Discussionsupporting
confidence: 62%
“…ITPR3 singlenucleotide polymorphism rs2229634 could be indicative of an increased incidence in coronary artery aneurysm among youngsters [36]. Variants in LMNA are linked with lipodystrophy [37]. Combining previous research, these mRNAs identified by this study may possess tight links to CAD pathogenesis.…”
Section: Discussionsupporting
confidence: 62%
“…Thus, the prevalence of atherosclerotic cardiovascular events in these subjects ranged from 14% to 68% throughout the literature ( 12 , 36 39 ), which, although variable, is also clearly higher than that reported for the general population ( 40 ). In addition, a higher frequency of cardiac events has likewise been observed in non-R482 FPLD type 2 carriers in comparison with FPLD type 2 subjects with variants at the 482nd codon ( 37 , 41 , 42 ). In this sense, in our cohort, 32/81 patients with FPLD type 2 harboured R482 pathogenic variants in the LMNA gene.…”
Section: Discussionmentioning
confidence: 94%
“…Patients with congenital generalized lipoatrophy may suffer from hypertrophic cardiomyopathy, with or without hypertension, associated with ectopic cardiac fat and/or lipotoxicity (65,66). Pathogenic variants in LMNA are responsible for lipodystrophy syndromes with early atherosclerosis and/or with dilated cardiomyopathy, rhythm and/or conduction disorders and/or extensive calcifications of cardiac valves (67)(68)(69)(70)(71)(72). A regular cardiovascular screening, with cardiac ultrasound and stress test, and, if needed, coronary CT angiogram, 24-hour ECG monitoring, and/or cardiac MRI is required in most patients with lipodystrophy syndromes (7,8).…”
Section: Cardiovascular Signsmentioning
confidence: 99%
“…In Hutchinson-Gilford progeria, but also in FPLD2, early atherosclerosis is due not only to metabolic risk factors, but also to direct pro-senescent effects of LMNA pathogenic variants on endothelial and vascular smooth muscle cells (40,63,93,94). Clinical features of accelerated ageing are observed in patients with complex progeroid forms of LMNA-linked lipodystrophies, with a large continuum of severity between Dunnigan syndrome and Hutchinson-Gilford progeria (67,71). At the cellular level, LMNA pathogenic variants impair the fate of several mesodermal lineages, such as endothelial vascular cells (64), myoblasts (95), cardiomyocytes (96), and adipocytes (97)(98)(99)(100)(101), and are involved in several signaling pathways which accelerate aging processes (102,103).…”
Section: Lipodystrophy and Ageingmentioning
confidence: 99%